EVALUATION OF WARFARIN ORAL USED BY INTERNATIONAL NORMALIZED RATIO VALUE AND DETERMINATION FREQUENCY TO CARDIOVASCULAR PATIENT AT HAJI ADAM MALIK GENERAL HOSPITAL, MEDAN, INDONESIA - Pertiwi, Dewi; Suwarso, Edy; Manik, Parlindungan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to evaluate of warfarin oral used by value and determination frequency of international normalized ratio (INR). Methods: The data of cardiovascular patients were collected from medical records in Haji Adam Malik General Hospital, Medan, North Sumatera, Indonesia, in 2016. This study evaluated the data by retrospective study design. The sample study was selected by Slovin method from the population of medical record of cardiovascular patients who received warfarin therapy. The sample of population was divided based on how many times the INR was measured. The groups are no measurement, once a year, unregularly schedule, thrice a year, and every month. The data were analyzed by analysis of variant to evaluated association of INR values and groups of patients. Result: The total sample in this study was 90 patients based on Slovin formula. The percentage of patient who never gets INR checked was 18.89%, once a year was 32.2%, unregularly was 34.44%, thrice a year was 8.89%, and every month was 5.56%. The value of INR in groups was 0.00 ± 0.00 in never checked group, once in year was 1.18 ± 0.44, unregularly was 1.79 ± 1.00, once time in 3 months was 2.04 ± 0.73, and every month was 2.42 ± 0.91. The groups of patients with never evaluation of INR value were significantly different with the other groups (p≤0.05). Conclusion: The results obtained in this study indicated the majority patients group in case of warfarin oral used and evaluation of bleeding status were once checked in year and unregularly determination of INR value. The best condition, in this case, was the determination of INR value in every month caused the bleeding or coagulation status of patient can be evaluated.